A New Biosensor to Enumerate Bacteria in Planktonic and Biofilm Lifestyle - Giusti, Maria De; Berlutti, Francesca; Pantanella, Fabrizio; Marinelli, Lucia; Frioni, Alessandra; Natalizi, Tiziana; Tufi, Daniela; Valenti, Piera (IntechOpen, 2011)
None